CURRICULUM MANAGEMENT BASED ON COLLABORATION AND INNOVATION: A STRATEGIC SOLUTION TO ANSWER THE CHALLENGE OF GRADUATES' QUALITY IN THE 21ST CENTURY - Hanipatin, Sri; Khoiri, Nur (Amanah Publishing, 2026)
This study aims to analyze the urgency and formulate a Collaboration- and Innovation-Based Curriculum Management model as a strategic solution to address the challenges of 21st-century graduate quality, as indicated by the low mastery of 4C skills (Critical Thinking, Creativity, Collaboration, and Communication) among students at SMP Negeri 40 Semarang. This research employs a qualitative case study approach, focusing on the analysis of collaboration and innovation concepts throughout the curriculum management cycle, from planning and implementation to evaluation. The synthesis of findings reveals that the low quality of graduates is primarily caused by curriculum management practices that are static, fragmented, and lack instructional innovation. The curriculum has not been managed collaboratively nor adapted to the demands of 21st-century learning. As a strategic solution, this study proposes the implementation of a participatory curriculum management framework by activating cross-disciplinary learning communities, as well as an adaptive approach through the mandatory integration of innovative learning models such as Project-Based Learning (PjBL) and Problem-Based Learning (PBL) supported by information and communication technology (ICT). The study concludes that improving the quality of graduates at SMP Negeri 40 Semarang can only be achieved through a paradigm shift in curriculum management toward a dynamic, collaborative, and innovative model aligned with the demands of 21st-century education.